Cultural and Socioeconomic Influences on Medicine Choice: A Comparative Review of Herbal and Pharmaceutical Drug Preferences and Their Implications for Health Policy - Kartiani, Andi (Yayasan Sinergi Kawula Muda, 2022)
Public perceptions of herbal and chemical medicine differ significantly between urban and rural populations, influenced by cultural traditions, education levels, economic status, and access to healthcare services. This study aims to analyze these differing perceptions and their implications for public health and regulatory policies. A systematic literature review was conducted using PubMed, Scopus, and Google Scholar, targeting peer-reviewed studies published in the past decade. The findings indicate that urban populations generally prefer pharmaceutical drugs due to their regulatory oversight and clinical validation, whereas rural communities rely more on herbal medicine due to affordability, accessibility, and cultural heritage. Regulatory challenges and inconsistent labeling standards have emerged as critical issues affecting public confidence in herbal medicine. Furthermore, healthcare professionals often lack sufficient knowledge of herbal medicine, limiting their ability to guide patients effectively. These disparities underscore the need for enhanced regulation, public education, and professional training in herbal medicine. The study recommends comprehensive policy interventions, including standardized clinical testing for herbal treatments and increased healthcare access in rural areas. Future research should focus on bridging the divide between traditional and modern medicine through integrative healthcare strategies. Strengthening regulatory frameworks and promoting education will be crucial in ensuring safe and informed medical choices.